Project-Based Learning Assisted by Moodle LMS Integrated with Maritime Industry for Soft Skills Development and Job Readiness of Maritime Vocational School Students - Wegig Pratama (Bulletin of Pedagogical Research, 2025)
This study aims to develop a Project-Based Learning (PjBL) model supported by the LMS Moodle integrated with the maritime industry to improve soft skills and work readiness of students of Maritime Vocational High Schools. The study used a Research and Development (R&D) approach with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 120 students, 24 teachers, and six maritime industry practitioners. Data were collected through questionnaires, interviews, FGDs, and observations of project activities. The results of expert validation showed a model feasibility level of 85% (very good category), covering aspects of content feasibility, LMS feature suitability, ease of use, and learning usability. Limited trials showed that the implementation of the PjBL model supported by the LMS Moodle had a positive impact on improving students' soft skills, especially in aspects of communication, cooperation, discipline, leadership, and problem-solving. The average skill improvement score reached 3.66 (very good category). Teacher and student responses to the model were also in the very positive category with an average of 87.8%. The integration of the Moodle LMS has been proven to facilitate digital collaboration between students, teachers, and industry practitioners, while also strengthening the relevance of learning to the needs of the workplace. Therefore, this learning model is deemed feasible, effective, and contextual for implementation in maritime vocational education in Indonesia.